Aplicación de contabilidad comercial en la empresa “Dispensa Ferretería” en la ciudad de Cuenca, periodo: noviembre – diciembre / 2015 - Martínez Meza, Julio Fabricio (2018)
The present research work is structured according to the requirements and regulations of the National University of Loja, prior to obtaining the degree of Accounting and Audit Engineer, at the same time, will allow to inform its owner an adequate accounting control of its economic activities, in relation to the legal regulations. During the investigation process, the proposed objectives were fulfilled, beginning with the preparation of the inventory of assets, rights and obligations, followed by the Plan and Manual of accounts and the verification of the supporting documents that were the basis for initiating the registration. accounting until obtaining the Financial Statements that provide information on the resources it has, the results it has obtained, the generated profit and the inflows and outflows of cash that it has derived, among other financial aspects. It concludes with the results obtained after having completed the investigative process it is possible to determine that with the elaboration of the accounting records the Financial Statements that provided information of the different accounting movements of the company are presented, recommending to continue with the Application of the Accounting that it will be an effective tool to organize the business accounting and in this way make decisions and alternative solutions for the different problems that affect the hardware store.